Investigation of relationship between tau PET SUVR and an indicator of post‐translational modification of tau in human blood plasma using electrochemical assay. (20th December 2022) - Yoon, Hyosang; Kwon, SunSang; Jeong, Seongeun; Hwang, Bo Song; Seo, Sang Won; Lee, Soo Hyun
Abstract: Background: Human tau protein is a well‐known biomarker to predict and diagnose the progress of Alzheimer's disease [1]. The tau protein undergoes various post‐translational modificiation (PTM) of tau such as phosphorylation, O‐glycosylation, nitration, and glycation. Recently, abnormal phosphorylation of tau protein is observed in AD patients, while the level of O‐GlcNAcylation on tau protein is relatively elevated in brains of normal controls [2]. Reference: [1] L.M. Ittner et al. Nature Reviews Neuroscience, 12 (2011) 67. [2] C. Alquezar et al. Frontiers in Neurology, 11 (2021) 595532: Method: (Figure 1) To investigate tau protein in human blood plasma and its PTM, a novel type of electrochemical sensor demonstrated and obtained Taumeter, an indicator as relative impedance changes of phosphorylated tau and O‐glycosylated tau, using secondary antibodies Finally, the as‐obtained Taumeter and PET SUVR were investigated for a relationship. Result: We investigated the clinical relationship between Taumeters for AT8 and AT270 and tau PET SUVR, respectively, obtained from human blood plasma from normal control (NC, n=9), mild cognitive impairment (MCI, n=14), and Alzheimer's disease (AD, n=13). In the case of AT8, it was observed that average Taumeters in MCI and AD were 2.86 and 4.73 times higher than those in NC ( p =0.078 between NC and AD) (Figure 2a). In the case of AT270, average Taumeters in MCI and AD were 1.84 and 4.24 times higher than those in NC ( p =0.057 between NC and AD) (Figure 2b). In further study, Taumeters for AT8 and AT270 correlated with tau PET SUVR ( r =0.151, p =0.384 and r =0.575, p <0.001) (Figure 2c‐d). Conclusion: In this study, we investigated Taumeter reflecting PTM of tau proteins using secondary antibodies (O‐GlcNAc antibody, AT8, and AT270) in human blood and tau PET scan to investigate the relationship of Taumeter and tau PET SUVR in NC, MCI, and AD. As a result, it can be carefully implied that Taumeter has the relationship with the progress of AD.